Vera Candiani. Dreaming of Dry Land. Environmental transformation in Colonial Mexico City. Stanford (California): Stanford University Press, 2014. 408 pp.: “A propósito de la reseña de Katherinne Giselle Mora Pacheco”. Por Vera Candiani - Mora Pacheco, Katherinne Giselle; Candiani, Vera (Fronteras de la historia, 2017)
.